Vitiligo in the 19th-century dermatological works of Vincenzo Chiarugi, Robert Willan, Jean-Louis Alibert, and Ferdinand von Hebra (Dermatology Reports, 2024)
Vitiligo is an iconic dermatological pathology, as its clinical manifestations indelibly mark the patient through the appearance of white spots all over the body. The oldest written testimonies referring to vitiligo are the first texts of Ayurveda, the Ebers Papyrus, and the Leviticus of the Old Testament. During the Roman Empire, the doctors Aulus Cornelius Celsus and Galen, respectively, in the I and II centuries AD, were the first to describe this skin disease, and their statements were used by all subsequent authors. Hieronymus Mercurialis in the XVI century, Joseph Jakob Ritter Plenck in the XVIII century, and Vincenzo Chiarugi again in the XIX century based their writings on the references of the two Roman doctors. After centuries of scientific inaction in the XIX century, there was an exponential increase in dermatological studies, and the medical-scientific works produced in this period laid the foundations of modern dermatology. The nineteenth-century texts of Robert Willan and Thomas Bateman, Jean-Louis Alibert, Ferdinand von Hebra, and Moriz Kaposi proved fundamental for the study of skin pathologies, including vitiligo. The nineteenth-century medical-scientific vision and approach to vitiligo are shown in this work through the presentation of direct quotes extrapolated from the most important works of the authors mentioned above; this served to historically contextualize the gradual progress of medical study regarding this skin pathology.